Impact of surgical margins on local control in patients undergoing single‐modality transoral robotic surgery for HPV‐related oropharyngeal squamous cell carcinoma. Issue 8 (15th April 2021) - Holcomb, Andrew J.; Herberg, Matthew; Strohl, Madeleine; Ochoa, Edgar; Feng, Allen L.; Abt, Nicholas B.; Mokhtari, Tara E.; Suresh, Krish; McHugh, Christopher I.; Parikh, Anuraag S.; Sadow, Peter; Faquin, William; et al.
Abstract: Background: The impact of close surgical margins on oncologic outcomes in HPV‐related oropharyngeal squamous cell carcinoma (HPV + OPSCC) is unclear. Methods: Retrospective case series including patients undergoing single modality transoral robotic surgery (TORS) for HPV + OPSCC at three academic medical centers from 2010 to 2019. Outcomes were compared between patients with close surgical margins (<1 mm or requiring re‐resection) and clear margins using the Kaplan–Meier method. Results: Ninety‐nine patients were included (median follow‐up 21 months, range 6–121). Final margins were close in 22 (22.2%) patients, clear in 75 (75.8%), and positive in two (2.0%). Eight patients (8.1%) recurred, including two local recurrences (2.0%). Four patients died during the study period (4.0%). Local control ( p = 0.470), disease‐free survival ( p = 0.513), and overall survival ( p = 0.064) did not differ between patients with close and clear margins. Conclusions: Patients with close surgical margins after TORS for HPV + OPSCC without concurrent indications for adjuvant therapy may be considered for observation alone.